2009
DOI: 10.1002/adfm.200800789
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Fading Mechanism in All Solid‐State Lithium Polymer Secondary Batteries Using PEG‐Borate/Aluminate Ester as Plasticizer for Polymer Electrolytes

Abstract: Solid‐state lithium polymer secondary batteries (LPB) are fabricated with a two‐electrode‐type cell construction of Li|solid‐state polymer electrolyte (SPE)|LiFePO4. Plasticizers of poly(ethylene glycol) (PEG)‐borate ester (B‐PEG) or PEG‐aluminate ester (Al‐PEG) are added into lithium‐conducting SPEs in order to enhance their ionic conductivity, and lithium bis‐trifluoromethansulfonimide (LiTFSI) is used as the lithium salt. An improvement of the electrochemical properties is observed upon addition of the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 27 publications
5
72
0
Order By: Relevance
“…[5,6] Recently, we fabricated an all-solid-state LPB with Li j SPE j LiFePO 4 constructions: This LPB showed degradation after tens of stable cycles arising from anion decomposition at the electrode surface at elevated temperature (60 8C). [7] Hence, we infer that the reduced anion mobility (or higher transport number) is attractive, because it suppresses the polarization (or overconcentration) of anions at the electrode j electrolyte interface during steady-state charging (concentration gradients of anions at the interface are reduced by the decreasing relative anion diffusivity at the steady state). Therefore, the addition of plasticizers with Lewis acidity may be important to realize long-life batteries.…”
Section: Introductionmentioning
confidence: 98%
“…[5,6] Recently, we fabricated an all-solid-state LPB with Li j SPE j LiFePO 4 constructions: This LPB showed degradation after tens of stable cycles arising from anion decomposition at the electrode surface at elevated temperature (60 8C). [7] Hence, we infer that the reduced anion mobility (or higher transport number) is attractive, because it suppresses the polarization (or overconcentration) of anions at the electrode j electrolyte interface during steady-state charging (concentration gradients of anions at the interface are reduced by the decreasing relative anion diffusivity at the steady state). Therefore, the addition of plasticizers with Lewis acidity may be important to realize long-life batteries.…”
Section: Introductionmentioning
confidence: 98%
“…The reaction voltages were observed around 3.4 V between charging and discharging, which agrees with previous results for the two-phase coexistence reaction in an olivine LiFePO 4 cathode. 7), 8) The corresponding capacity retention, Coulombic efficiency, and quasi-polarization with cycle numbers are shown in Figs. 5(a)5(c), respectively.…”
Section: Jcs-japanmentioning
confidence: 99%
“…Our previous results showed that the decrease in the Li concentration at the SPE/LiFePO 4 interface was caused by the decomposition of the TFSI anion. 8) Thus, the film formed on the cathode particles contained products of the TFSI decomposition.…”
Section: Jcs-japanmentioning
confidence: 99%
See 2 more Smart Citations